Evaluation of the mental problems of menopausal women referred to the health care centers of Ilam University of Medical Sciences - Rasooli; F. Haj Amiry; P. Mahmoudi; M. Shohani; M. (Tehran University of Medical Sciences, 2004)
Introduction: Menopause, the permanent cessation of menstruation, is an important event in the long process of climactrium, signaling a change from the years of fertility to infertility. Postmenopausal women have many physical and mental problems. Materials and Methods: The objective of this study was to determine the mental problems of menopausal women referred to the health care centers of Ilam University of Medical Sciences in 2003. The research tools in this analytical-descriptive study were a questionnaire, record sheet and standard tests composed of Beck and Cattle scales. The data were collected by interview. The samples consisted of 150 menopausal women who had been selected by random sampling method. The data analysis was done by SPSS software. Results: The results showed that short-term memory disorder (39.3%), mild depression (32%) and mild anxiety (27.7%) were the most common mental problems. There was a significant relationship between depression and marital status (p=0.029) and having knowledge about menopause (p = 0.04). Anxiety had no relationship with any variables (p>0.05) but there was an association between depression and anxiety (p = 0.002). Conclusion: The findings show that the menopausal women suffer from mental problems, which influence their quality of life and community health. Thus, planning educational and health care programs to help them overcome these obstacles is essential.